2020
DOI: 10.30994/sjik.v9i2.258
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis of Hypertension Occurrence Based on Urban-Rural Location in Indonesia (IFLS Data Study 5)

Abstract: The World Health Organization (WHO) defines hypertension as a "silent killer" disease because the most of hypertension has not signs or symptoms. Nationally, Indonesia in 2016, the prevalence of hypertension is also higher in urban areas by 31.7% than in rural areas by 30.2%, the prevalence of hypertension is increasing with the increasing of ages. This study aims to analyze the factors that influence the incidence of hypertension and to determine the most influential factor at risk in the incidence of hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The results of this study are supported by research that states that adolescents exposed to any type of tobacco smoke are likely to experience an increase in blood pressure compared to adolescents who are not exposed to tobacco smoke, with an odds ratio of 1.31 (95 % CI 1.01-1.61) (22). Another study conducted in rural areas showed that tobacco use and exposure to cigarette smoke are significant risk factors associated with increased blood pressure in adolescents in rural areas (17,23). However, the results of this study contradict several studies which state that there is no significant relationship between smoking and hypertension or increased blood pressure in adolescents (24)(25)(26)where were randomly selected from Junior High Schools in Central Jakarta.…”
Section: Discussionsupporting
confidence: 55%
“…The results of this study are supported by research that states that adolescents exposed to any type of tobacco smoke are likely to experience an increase in blood pressure compared to adolescents who are not exposed to tobacco smoke, with an odds ratio of 1.31 (95 % CI 1.01-1.61) (22). Another study conducted in rural areas showed that tobacco use and exposure to cigarette smoke are significant risk factors associated with increased blood pressure in adolescents in rural areas (17,23). However, the results of this study contradict several studies which state that there is no significant relationship between smoking and hypertension or increased blood pressure in adolescents (24)(25)(26)where were randomly selected from Junior High Schools in Central Jakarta.…”
Section: Discussionsupporting
confidence: 55%